(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Today’s fast-growing technology, "Cloud computing," is widely employed in various industries because to its low-cost services, such as pay-per-use mode, which allows users to access resources via an Internet connection. Cloud storage is a service offered by cloud service providers that allows users to store their data on a remote server. Although cloud service providers ensure that data kept in the cloud will be safe and secure, there are a number of issues that must be addressed. For user data in the cloud, data integrity and security must be assured. The integrity of the data must be unmistakable. There are some security dangers associated with storing sensitive data with cloud storage companies. The lack of data integrity is a big worry in the cloud environment. Encryption computations are used to provide complete security of data being sent from one source to another, as well as to prevent private data from being exposed to unauthorized parties. Encryption computations are mostly useful for obtaining and protecting information being sent from one end to the next from any type of flaw. Some of these computations have been adopted by scientists to ensure data security in banking, healthcare, and the military. When used for information security, a fraction of these computations are varied in terms of effectiveness, exactness, dependability, and reaction time. We considered Rivest-Shamir-Adleman (RSA), Advanced Encryption Standard (AES), BLOWFISH, and Data Encryption Standard (DES) calculations in order to conduct a relative evaluation. Because there is scepticism about which of the computations is more reliable, trustworthy, and practical when considering the highlights that depicted their variety. As a result, this work aims to conduct a close examination of each encryption calculation in order to determine the optimal method for employing the specified measures. Python was used to implement modify BLOWFISH’s algorithm. When the results are compared to other algorithms results, it is discovered that BLOWFISH takes the shortest time to encrypt, while RSA and AES take the longest. In addition, based on the measurements used in the evaluation, the BLOWFISH calculation is regarded as the most proficient of the three calculations. In this study, only a few of the obtained results are discussed.